2004
DOI: 10.1002/rcm.1518
|View full text |Cite
|
Sign up to set email alerts
|

Electrospray ionization mass spectrometric characterization and quantitation of xanthine derivatives using isotopically labelled analogues: an application for equine doping control analysis

Abstract: Isotope-dilution mass spectrometry has been employed successfully in numerous fields of analytical chemistry enabling the establishment of fast and reliable procedures. In equine sports, xanthine derivatives such as caffeine and theobromine are prohibited, and doping control laboratories analyze horse urine specimens regarding these illicit performance-enhancing drugs. Theobromine has to exceed a threshold level of 2 microg/mL, hence a robust and reliable quantitation is required. Stably deuterated theobromine… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
34
0
2

Year Published

2004
2004
2021
2021

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 28 publications
(39 citation statements)
references
References 22 publications
3
34
0
2
Order By: Relevance
“…Some comparative studies show that many similarities exist between CID fragments and those which are formed in a collision chamber, particularly when comparing fragmentations of pure protonated molecules . Spectra obtained from preliminary CID fragmentation experiments with caffeine revealed a very close similarity to a published spectrum whose fragments had been generated by means of a collision chamber . Intrigued by this study, it was our aim to gain a deeper insight into the pure CID fragmentation chemistry of xanthine derivatives.…”
Section: Resultsmentioning
confidence: 73%
See 3 more Smart Citations
“…Some comparative studies show that many similarities exist between CID fragments and those which are formed in a collision chamber, particularly when comparing fragmentations of pure protonated molecules . Spectra obtained from preliminary CID fragmentation experiments with caffeine revealed a very close similarity to a published spectrum whose fragments had been generated by means of a collision chamber . Intrigued by this study, it was our aim to gain a deeper insight into the pure CID fragmentation chemistry of xanthine derivatives.…”
Section: Resultsmentioning
confidence: 73%
“…For the investigation of the fragmentation chemistry of xanthine derivatives in the ESI‐MS mode, in addition to other unlabeled xanthines, a deuterated isotopomer of caffeine has been described and examined . For fragmentation experiments the authors of this work have used a collision cell; however, such a cell is not available in small and simple mass spectrometers.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The characterization of caffeine and its major metabolites in biological fluids by HPLC-MS and CE has been reported in the literature by various laboratories (see Table 2, [74][75][76][77]); however, the HPLC data differ from the data obtained by CE in several ways: (a) some differences in the migration order or separation of the analytes studied were observed; (b) the LC method was laborious; for example, one laboratory reported that in order to obtain the characterization of all caffeine metabolites using LC-MS/MS, two instrument runs for each sample tested were required, one for the negative ionization mode and another for the positive mode [75]; and (c) a significant difference can be observed in the amount of organic solvents and reagents consumed. Although not tested in this laboratory, CE has the potential for assaying a large number of samples when multicapillary CE instruments are employed [78].…”
Section: Figurementioning
confidence: 99%